Working environment. Considerations for a Higher Education Institution - Parrales Poveda, María Leonor; Rodríguez Gutiérrez, Kelly Gabriela; Sornoza Parrales, Diego Renato; Fienco Parrales, María José (Revista Venezolana de Gerencia, 2023)
Teachers’ work is influenced by their perception of their work environment, projecting this into the quality of education and product delivered to society. Therefore, this study analyzes how the work environment manifests itself in a Higher Education Institution, considering affiliation, commitment, communication, motivation, recognition, and other factors that affect the performance of a university teacher. The results show that teachers’ perceptions of their work environment are internally differentiated, with factors such as commitment, internal communication, recognition, empathy, physical integrity at work, remuneration, joint participation between work teams, and authority having negative connotations. A suggestion for improvement is executing plans designed to generate an effective organizational change in the detected weaknesses.